BIOLOGIC THERAPY IN CROHN’S DISEASE: MECHANISMS, TREATMENT OPTIONS AND ADVERSE EFFECTS - Karolina Paks; Monika Pelczar; Zuzanna Gajda; Barbara Starosta; Bartosz Brzychcy; Karolina Brzychcy; Natalia Musialik; Ewa Jench; Maciej Magiera (International Journal of Innovative Technologies in Social Science, 2025)
Background and aim: Crohn’s disease (CD) is a chronic inflammatory bowel disease that can involve any segment of the gastrointestinal tract. It is characterized by a relapsing-remitting clinical course, significantly impairing patients' daily functioning and quality of life. This article reviews the current evidence on biologic therapies for CD and discusses their practical application in primary care settings.Material and methods: This study was based on an analysis of the guidelines issued by the Polish Society of Gastroenterology and the National Consultant in Gastroenterology, along with the updated B.32 drug program (effective February 2024). Additionally, a systematic review of available scientific literature from the PubMed database was conducted. The article selection process utilized the following search terms: "Crohn's disease," "biological treatment," and "Crohn's disease treatment."Results: The treatment of Crohn’s disease is chronic and initially relies on conventional therapies, including glucocorticosteroids and immunosuppressants. In moderate-to-severe cases, biological medicines are introduced. Currently, five biologic drugs are approved for use in Poland: infliximab, adalimumab, vedolizumab, ustekinumab, and upadacitinib—the first oral biologic approved for CD treatment. Further research is needed to treat Crohn's disease patients more effectively.Conclusions: The rapid advancement of biologic therapies has significantly improved disease control, reduced reliance on steroids, and enhanced patient outcomes. For primary care physicians, recognizing the typical adverse effects of biologics and differentiating them from CD exacerbations is essential for effective management.